Intended meaning of Coldplay’s album cover “A Head Full of Dreams”: semiotic study - Nur Fadilla; Dwi Setiyadi; Rosita Ambarwati (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
The study entitled “Intended Meaning of Coldplay’s Album Cover “A Head Full of Dreams”: Semiotic Study”. The data taken from Coldplay album cover. The aims of this study is to describe semiotic elements and to describe the meaning intended in the album cover. The data analysis described in qualitative using semiotic theory from Peirce icon, index, and symbol. Then, to represent the meaning and the ideas used theory ideology from Dijk. The results shows that theory of semiotic succeed to describe the meaning intended in album cover. The visual and verbal elements have functions to persuade the people to buy Coldplay album A Head Full of Dreams.